Infectious events in kidney transplant recipients from deceased expanded criteria donors: a prospective cohort - Sirlei Regina de Sousa; Cassiane Dezoti da Fonseca; Monica Taminato; Maria de Fatima Fernandes Vattimo; Angélica Gonçalves Silva Belasco; Álvaro Francisco Lopes de Sousa; Inês Fronteira; Dulce Aparecida Barbosa
ABSTRACT Objective: Analyze risk factors for infection in kidney transplant recipients from deceased expanded criteria donors (DECD) in the first two years of follow-up. Method: This is a prospective cohort study with 466 patients from DECD who underwent kidney transplantation in 2015 and 2016 in Brazil. A total of 551 events were recorded. The largest incidence of infectious events occurred in the first month after kidney transplantation. Cytomegalovirus infection was the most common infectious episode. Results: The incidence rate of infections was 57.1%. Among bacterial infections, only 4% were due to multidrug-resistant microorganisms. The death rate was 3.3% (15) patients. The main cause of death was infectious (73.3%). Hospitalization until the first infection (aOR:1.61), Number of infections in 1 year (aOR:40.16), and Cytomegalovirus infection (aOR:13.84) was risk factors for infection by multidrug resistant microorganisms (MDR). Conclusion: Infection incidence with MDR bacteria was high among kidney transplant recipients from DECD, and the main cause of death was infection. Survival was high among patients with infection.